Orthoplastic Approach to Extremity Reconstruction: A Paradigm Shift in Integrated Limb Salvage - Lin, Cheng-Hung; Chou, Ying-Chao; Hsu, Chung-Chen; Huang, Ren-Wen; Lin, Chih-Hung (Seminars in Plastic Surgery, 2025)
The orthoplastic approach to extremity reconstruction represents a paradigm shift in the management of complex limb injuries, integrating orthopedic and plastic surgery principles to optimize functional and aesthetic outcomes. This review examines the evolution of this approach, its hierarchical framework for addressing tissue defects, and the essential technical competencies required for successful implementation. Key components of orthoplastic extremity reconstruction are illustrated through current evidence focusing on soft tissue management with high free flap success rates, vascularized bone transfers utilizing fibula, iliac crest, and medial femoral condyle flaps, and advanced techniques for amputee reconstruction including regenerative peripheral nerve interfaces and targeted muscle reinnervation. Meta-analysis evidence demonstrates that the synergistic collaboration between orthopedic and plastic surgery specialties achieves significant reduction in infection rates, improved limb salvage rates, and decreased health care costs through reduced hospital stay and revision surgeries. This article emphasizes the importance of multidisciplinary collaboration, comprehensive preoperative planning, and technical expertise in achieving optimal results in complex extremity reconstruction while addressing recent advances in reconstructive microsurgery protocols.
Keywords: orthoplastic reconstruction; extremity reconstruction; vascularized bone transfer